Pedagogy Over Technology: Animal-Themed Digital Games to Support Early Mathematics Learning - Fathanah, Nurul; Syarfina, Syarfina; Nadhirah, Nadhirah; Kamis, Kamis; Mahriza, Rita; Maisari, Sri (Atfaluna Journal of Islamic Early Childhood Education, 2025)
This study aims to develop and evaluate "Smartimals," an animal-themed digital game designed to support early mathematics learning in resource-limited contexts. Employing a Research and Development (R&D) approach adapted from the 4-D model, the study was conducted with 15 children aged 5–6 years in a rural area of East Aceh, Indonesia. The development prioritized accessible technology to ensure practicality for teachers in infrastructure-constrained settings. Data were collected through expert validation questionnaires and direct observation of learning outcomes. The results indicate that the developed media is highly feasible and effective, achieving expert validation scores of 95.3% for media design, 80% for content, and 96% for language, alongside a field trial effectiveness rate of 89.9%. Beyond technical feasibility, the findings suggest that the integration of familiar animal themes functions as a cognitive anchor, effectively reducing extraneous cognitive load and bridging abstract mathematical concepts, such as arithmetic and pattern recognition, with concrete experiences. This study reinforces the premise of "pedagogy over technology," demonstrating that simple, contextually relevant ICT tools can significantly enhance early numeracy and student engagement, offering an inclusive solution for early childhood education in remote areas.